2012
DOI: 10.1158/0008-5472.can-11-2254
|View full text |Cite
|
Sign up to set email alerts
|

PRAS40 Is a Functionally Critical Target for EWS Repression in Ewing Sarcoma

Abstract: Ewing sarcoma family tumors (ESFT) are highly aggressive and highly metastatic tumors caused by a chromosomal fusion between the Ewing sarcoma protein (EWS) with the transcription factor FLI-1. However, expression of the EWS/FLI-1 chimeric oncogene by itself is insufficient for carcinogenesis, suggesting that additional events are required. Here, we report the identification of the Akt substrate PRAS40 as an EWS target gene. EWS negatively regulates PRAS40 expression by binding the 3 0 untranslated region in P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…This triggers protein stabilization of the tumor suppressor p53, leading to cell cycle arrest, senescence, or apoptosis mediated by p53’s transcriptional targets. 36, 8, 46, 47 Because PRAS40 displays pro-survival 30, 34, 35 and pro-tumorigenic 29, 31 activity through an unknown mechanism, we hypothesized that PRAS40 negatively regulates p53 through association with RPL11 and inhibition of the RPL11-HDM2-p53 pathway. To explore this possibility, we depleted U2OS human osteosarcoma cells of PRAS40 using shRNAs targeted to various regions of the PRAS40 transcript.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This triggers protein stabilization of the tumor suppressor p53, leading to cell cycle arrest, senescence, or apoptosis mediated by p53’s transcriptional targets. 36, 8, 46, 47 Because PRAS40 displays pro-survival 30, 34, 35 and pro-tumorigenic 29, 31 activity through an unknown mechanism, we hypothesized that PRAS40 negatively regulates p53 through association with RPL11 and inhibition of the RPL11-HDM2-p53 pathway. To explore this possibility, we depleted U2OS human osteosarcoma cells of PRAS40 using shRNAs targeted to various regions of the PRAS40 transcript.…”
Section: Resultsmentioning
confidence: 99%
“…29, 31 To clarify the tumorigenic function of PRAS40 we have interrogated its subcellular localization and interactome. Here we experimentally demonstrate that PRAS40 subcellular distribution is controlled at least in part by Crm1-dependent nuclear export directed by a NES sequence - 218 IAASMRALVL 227 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EWS has not previously been implicated in tumor suppression except that it has been shown to control cell proliferation via posttranscriptional regulation of the Akt substrate PRAS40. 53 Dysfunction of REST is evident in several cancers and is achieved through diverse mechanisms. In prostate cancer, loss of REST results in the derepression of IB1/JIP1 (Islet-Brain1/c-Jun amino-terminal kinase interacting protein 1) to prevent JNK activation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of PRAS40 or inhibition of its upstream Akt3 decreases the anchorageindependent growth of cells in culture and tumor development in mice (51). Similar findings were reported in breast and lung cancer cells (52). Kazi et al showed that silencing PRAS40 reduced proliferation of C2C12 cells due to a cell cycle arrest in the G 1 phase (53).…”
Section: Discussionmentioning
confidence: 58%